PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DENGAN TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) PADA MATERI SISTEM ENDOKRIN MANUSI - Aspatita Yuliani Panjaitan; Erlintan Sinaga; R Rasmi (Jurnal Pelita Pendidikan, 2020)
This research is aimed to know the difference of students’ learning scores who were taught by using cooperative Jigsaw dan STAD (Student Team Achievement Division) model in the endocrine system of human body material in grade XI MIA SMA Negeri 7 Medan year of academic 2017/2018. This research is design as an experimental. The population of this research is 72 students, and the sample was taken by random sampling, which  XI IPA 1 class (as Jigsaw class) there are 36 students and XI IPA 2 class (as STAD class) there are 36 students. The data is collected by using a multiple-choice question test consist of 30 items and an observation sheet. Based on the analysis requirements data, the average value of students’ learning scores in the Jigsaw model at 84,84 with SD 9,06 and students’ learning scores in the STAD model at 79,88 with SD 8.96. From the data obtained it is known that the average value of the Jigsaw class is higher than the STAD class. The results of hypothesis testing using t-test at a significant level of 0.05, can the two classes differ significantly.